Sarcopenic Obesity: Prevalence and Association With Metabolic Syndrome in the Korean Longitudinal Study on Health and Aging (KLoSHA) - Lim, Soo; Kim, Jung Hee; Yoon, Ji Won; Kang, Seon Mee; Choi, Sung Hee; Park, Young Joo; Kim, Ki Woong; Lim, Jae Young; Park, Kyong Soo; Jang, Hak Chul (Diabetes care, 2010)
We investigated the prevalence of sarcopenic obesity (SO) and its relationship with metabolic syndrome in a community-based elderly cohort in Korea. In this study, 287 men and 278 women aged 65 or older were recruited. Sarcopenia was defined as the appendicular skeletal muscle mass (ASM) divided by height squared (Ht(2)) (kg/m(2)) or by weight (Wt) (%) of <1 SD below the sex-specific mean for young adults. Obesity was defined as a visceral fat area >or=100 cm(2). The prevalence of SO was 16.7% in men and 5.7% in women with sarcopenia defined by ASM/Ht(2); however, it was 35.1% in men and 48.1% in women by ASM/Wt. Using ASM/Wt, the homeostasis model assessment of insulin resistance of subjects with SO was higher and they were at higher risk for metabolic syndrome (odds ratio [OR] 8.28 [95% CI 4.45-15.40]) than the obese (5.51 [2.81-10.80]) or sarcopenic group (2.64 [1.08-6.44]). SO defined by ASM/Wt was more closely associated with metabolic syndrome than either sarcopenia or obesity alone.